Dynamic Hybrid Multiple Attribute Decision-Making Problem Based on Reference Point Adaptation. (29th November 2019) - Ma, Wei-Min; Zhang, Hui; Sun, Bing-Zhen; Wang, Neng-Li; Zhao, Hai-Yan
Abstract : Individuals' decision-making depends on reference points in prospect theory. This research considers the bounded rationality of decision makers and constructs a dynamic hybrid multiple attribute decision-making (DHMADM) model. Unlike existing models, the DHMADM model focuses on dynamic reference point, which has been proven in prospect theory. This research presents the effects of reference point adaptation on decision-making through model calculation. The optimal choice of decision makers changed with the change of the reference point in the DHMADM model. By experiment, we found that the DHMADM model considering reference point adaptation can more accurately express the final choice of decision makers than models only considering the static reference point.